Les jardins du Carrousel (Paris) De la campagne à la ville : la formation d'un espace urbain - Van Ossel, Paul (Documents d'archéologie française, 1998)
An OverView is presented here of the studies conducted at this prestigious site, where as a rural, then an urban space developed. the traces left by humankind from prehistoric times to the 19th century have accumulated. The trenches and material of farmers of Neolithic and protohistoric times gave way to a silt quarry, then to the plots of land in a suburbium outside of Lutetia, still present in the 9th century. A 14th century manor house, decorated with mural paintings, preceded the city's encroachment on this area, seen in the Charles V city wall and the neighbouring faubourg, while the tile Works continued to be active for three centuries. In the 16th century the site was drastically altered by the construction of the Tuileries castle and the Jardin Neuf. Interpretation of the numerous vestiges, supported by palaeoenvironmental studies and archival documents, provides new and sometimes unexpected data on land use before urbanisation, on the social status of the inhabitants, on the fate of renowned edifices. This book tells a story. "the story of a small piece of Paris", one of the great seats of the history of France. In the heart of Paris, the Grand Louvre project led to urban excavation on an exceptional scale. This archaeofogical operation was a model of its kind, both by the nature of its findings and its state-of-the-art exploration strategies.